Finite Element Analysis of the Maximum Stress at the Joints of the Transmission Tower - Itam Z.; Beddu S.; Mohd Kamal N.L.; Bamashmos K.H. (Institute of Physics Publishing, 2023)
Electric power transmission; Static analysis; Towers; Beam elements; Joint analysis; Maximum stress; Overhead power lines; Steel lattice; Stress values; Tall structures; Transmission tower; Finite element method; engineering; finite element method; fixed structure; joint; research work; software; statistical analysis; steel; stress